ANALYSIS OF THE PHILOSOPHICAL AND ETHICAL HERITAGE OF ALISHER NAVOY IN THE CREATION OF TURKISH SCIENTISTS (TAMADDUN NURI JURNALI, 2024)
This article talks about the opinions expressed by Turkish scientists regarding the moral, religious and philosophical views found in Alisher Navoi's work, as well as the researches carried out until today. We know that Navoi's work is a precious gem. No matter how we study his legacy, it will be refined over the years and lead us to the world of unexpected meanings. This article also talks about how the socio-philosophical views of Hazrat Alisher Navoi's work have been analyzed by fellow Turkish scientists. In this regard, reference is made to the monograph "Alisher Navoi" by Turkish literary scholar Ogoh Sirri Levend and the articles "Study of Alisher Navoi in Turkey" by Vahid Turk.